Analisis Kualitas Pelayanan Frontliner terhadap Kepuasan Nasabah Bertransaksi di Bank Sumut Syariah Kantor Cabang Pembantu Marelan Raya - Hilwatun Nawrah; Ahmad Perdana Indra (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This research examines the analysis of frontliner service quality on customer satisfaction with transaction at Bank Sumut Syariah KCP Marelan Raya. This research aims to understand the quality of frontliner service on customer satisfaction, as well as analyze the ompact on customer and what is more about this sharia bank. The method in this research is qualitative which also involves documentation analysis and interviews with the bank. The results of the research show that Bank Sumut Syariah has provided a very good level of service but still needs to improve sevice to customer to minimize risk that may aris in the future. It also needs to be avoided so that analyzing customer complaints should not be done alone to avoid the emergence of non-objective assessments of customer.